Peculiarities of primary school children’s behaviour and their test anxiety - Augis, R. (Psichologija, 1988)
The test anxiety of 68 eight-year-olds has been conducted with the help of S. B. Sarason’s "The Test Anxiety Scale for Children". The peculiarities of their behaviour in stress situations at school have been studied through clinical interviews and observations. The analysis of the data obtained has confirmed our hypothesis (p<0.01) that an increase in test anxiety is related to unrealistic behaviour which is psychologically based on impulsiveness and psychological defence mechanisms, whereas a relative decrease in lest anxiety is linked with realistic behaviour which is psychologically based on will.